Correlation between Anatomical Variations of Lower Pelvicalyceal System and Isolated Lower Pole Calculus Formation Compared with Non-stone Bearing Contralateral Kidney: Case Control Study - Sharma, Prakash; Lalchan, Subita; KC, Subash; Gyawali, Merina; Poudel, Aseem; Kushwaha, Niraj (Nepal Journal of Medical Sciences, 2022)
Introduction: Renal calculus is one of the common problems frequently encountered in clinical practice. Various factors play an important role in its formation.This study was done to find out the anatomical variations of the lower pole of the kidney bearing the calculus and compared it with the calculus-free contralateral kidney. Method: Patients with isolated lower pole calculus undergoing computed tomography urography and computed tomography of the abdomen and pelvis were included in the study. Infundibuloureteropelvic angle, infundibulocalyceal length, and infundibular width of the lower calyx of the stone-bearing kidney were measured and compared with the contralateral stone-free kidney. Result: A total of 37 patients were included for statistical analysis. The age of the patients ranged from 22 to 84 years with a mean age of 41.9±17.9 years. Infundibulocalyceal length (ICL) of the calculus-bearing kidney was significantly longer than the calculus-free kidney. Infundibuloureteropelvic angle (IUPA) of the calculus-bearing kidney was significantly more acute than a calculus-free kidney. There was no significant difference in infundibular width between the calculus bearing and calculus free kidney Conclusion: IUPA and ICL are significantly associated with lower pole calculus.